2012
DOI: 10.1136/annrheumdis-2011-200298
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, pharmacokinetics, pharmacodynamics and efficacy of the monoclonal antibody ASK8007 blocking osteopontin in patients with rheumatoid arthritis: a randomised, placebo controlled, proof-of-concept study

Abstract: Osteopontin blockade is well tolerated and not related to safety concerns. These results consistently show that osteopontin blockade is unlikely to induce robust clinical improvement in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 34 publications
0
28
0
1
Order By: Relevance
“…Several studies have reported an association of the rs9138 A risk allele with low serum levels of soluble OPN 3 17. However, to date, the exact role of OPN in RA joint damage is controversial: distinct murine models of RA have shown conflicting results on the relevance of OPN in bone erosion pathogenesis,18 19 and, more importantly, OPN blockade was found to be unlikely to induce robust clinical improvement in patients with RA 20…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association of the rs9138 A risk allele with low serum levels of soluble OPN 3 17. However, to date, the exact role of OPN in RA joint damage is controversial: distinct murine models of RA have shown conflicting results on the relevance of OPN in bone erosion pathogenesis,18 19 and, more importantly, OPN blockade was found to be unlikely to induce robust clinical improvement in patients with RA 20…”
Section: Discussionmentioning
confidence: 99%
“…These studies highlight that the influence of inflammation on bone is specific to the site of inflammation and dependent on the cytokines present within the local bone microenvironment. It has also been shown that OPN has implications for inflammation involving osteoclasts, monocytes, lymphocytes, and neutrophils (37), and in fact, cumulative evidence suggests that OPN is involved in the pathogenesis of RA because it is important in both joint inflammation and destruction (38). The physiologic concentration of OPN is 20-35 ng/ml (39,40); however, high concentrations of OPN have been detected in RASFs and have even been known to induce chondrosarcoma cell migration (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…OPN is a Hh-target, and a matricellular protein that is highly upregulated in fibrotic skin, lungs, kidneys, and joints (2730). Mice genetically-deficient in OPN develop less fibrosis after certain injuries, suggesting that OPN may be a direct effector of the fibrotic process.…”
Section: Introductionmentioning
confidence: 99%
“…Despite prevailing data giving credence to OPN being an attractive anti-fibrotic target, and humanized antibodies to OPN being developed for inflammatory-joint diseases (30), no study has yet evaluated the impact of OPN neutralization in the treatment of fibrosis complicating CLD. Therefore, to evaluate these hypotheses, we studied the direct effects of OPN in cultures of liver progenitors, examined the effects of OPN-neutralization (by OPN-specific aptamers or OPN-neutralizing antibodies) in three murine models of liver fibrosis, and corroborated findings with analysis of liver tissues from patients with CLD.…”
Section: Introductionmentioning
confidence: 99%